Dammarane Triterpenes Targeting α-synuclein Biological Activity and Evaluation of Binding Sites by Molecular Docking - Melo-Hurtado, F; Caballero-Alvial, L (Taylor and Francis Ltd., 2021)
Parkinson s disease (PD) is a neurodegenerative disorder that affects adult people whose treatment is palliative. Thus, we decided to test three dammarane triterpenes 1, 1a, 1b, and we determined that 1 and 1a inhibit β-aggregation through thioflavine T rather than 1b. Since compound 1 was most active, we determined the interaction between α-synuclein and 1 at 50 µM (Kd) through microscale thermophoresis. Also, we observed differences in height and diameter of aggregates, and α-synuclein remains unfolded in the presence of 1. Also, aggregates treated with 1 do not provoke neurites retraction in N2a cells previously induced by retinoic acid. Finally, we studied the potential sites of interaction between 1 with α-synuclein fibrils using molecular modelling. Docking experiments suggest that 1 preferably interact with the site 2 of α-synuclein through hydrogen bonds with residues Y39 and T44. © 2020 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.